Analysis of Learning and Academic Performance of Education Students Before and During the Coronavirus Disease Pandemic - Andie Tangonan Capinding* (RU Publications, 2021)
The study focused on education students' learning experiences and the differences in their activities before and during the pandemic. This research was carried out at the NEUST Gabaldon Campus during the academic year 2020-2021 vacation. A study design that combines descriptive-comparative and descriptive-correlational elements. The descriptive-comparative design was used to compare the number of hours students spent sleeping, studying, using social media, and academic performance before and during the pandemic. The descriptive-correlation design, on the other hand, was used to determine the relationship between a student's academic performance (GPA) and the number of hours spent sleeping, studying, and using social media during the pandemic. The 171 education students who participated in the study were chosen through stratified random sampling. The findings revealed that there is a significant difference in the number of hours spent sleeping, studying, and using social media before and during the pandemic. However, there is no significant difference in students' academic performance before and during the pandemic. The study also discovered a highly significant link between the number of hours spent studying and academic performance and between the number of hours spent in social media and the number of hours spent studying. Nonetheless, there is no statistically significant relationship between students' academic performance and the number of hours they sleep and the use of social media during the pandemic. In addition, there is no link between the number of hours they sleep and the amount of time they spend studying and using social media. The students agree that there are benefits and drawbacks to flexible learning. The study's theoretical and practical implications were also discussed.